ANALYSIS OF FINAL-YEAR STUDENTS SELF-AWARENESS USING REFERENCE MANAGEMENT SOFTWARE - Avidiansyah, Zulfa; Kurniajaya, James Frederich (Record and Library Journal, 2020)
Background of the study: Academic environments such as universities have never been separated from the activities of scientific writing. In scientific writing, there is information that needs to be studied through various literature as a basis for writing. Literature as reference material in scientific papers needs to be managed so that it can be included in the bibliographic list according to the applicable rules. Management of bibliographic lists with various writing styles can be helped by using software assistance. Observations made by the authors at the Universitas Gadjah Mada (UGM) Graduate School Library, many of theses from students are still not appropriate in the procedure for writing the bibliography. So, it becomes a question of how the final level self-awareness of students in the use of citation/reference software.Purpose: Therefore, in this pilot study, the aim was to see and provide an initial description of the final-year students of self-awareness in the use of citations/reference management software.Method: Quantitative methods were used in this study and surveys were conducted to obtain data by adopting and modifying the Self-Awareness Outcomes Questionnaire (SAOQ) to measure student self-awareness.Findings: The results of the survey that have been carried out, the final level students of the Master of Culture and Media Study Program, the Graduate School of UGM have self-awareness in the use of citation/reference software.Conclusion: This researchcan be used as an initial step in further research and a reflection for libraries to always assist students.